A checklist of ciliates (Ciliophora) inhabiting on ostracods (Crustacea, Ostracoda) - Chatterjee, Tapas; Dovgal, Igor; Mayén-Estrada, Rosaura; Fernandez-Leborans, Gregorio (Zootaxa, 2020)
A compilation of the ciliated species found on freshwater and marine ostracods as epibiont or parasite (endobiont) has been carried out based on published records. The checklist includes the taxonomic position of each species of epibiontic and endobiontic ciliate, the species of basibiont ostracodes, the geographic zones and the bibliographic references where they were recorded. Altogether 7 suctorian, 29 peritrich, one apostome and one scuticociliatid species were listed. Two of recorded suctorian species are possible specific to marine ostracodes, whereas only one, Tokophrya sibirica to freshwater hosts. Fourteen species of peritrichs are likely specific to freshwater ostracodes, while three possible specific to marine ostracode hosts. Other suctorian and peritrich ciliate species were found on a variety of host taxa. One species of scuticociliatid was recorded as endobiont in ostracod.